2019
DOI: 10.1186/s13041-019-0517-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of RASopathy-associated mutations on CNS development in mice and humans

Abstract: The RAS signaling pathway is involved in the regulation of developmental processes, including cell growth, proliferation, and differentiation, in the central nervous system (CNS). Germline mutations in the RAS signaling pathway genes are associated with a group of neurodevelopmental disorders, collectively called RASopathy, which includes neurofibromatosis type 1, Noonan syndrome, cardio-facio-cutaneous syndrome, and Costello syndrome. Most mutations associated with RASopathies increase the activity of the RAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 221 publications
(370 reference statements)
1
36
0
Order By: Relevance
“…www.nature.com/scientificreports/ Cell type specific roles of RAS signalling in learning and memory. It has been shown that the RAS proteins are critically involved in learning and memory and synaptic plasticity 16,27 . Hyperactivation as well as hypoactivation of RAS-ERK signalling impairs learning and memory and synaptic plasticity 16,[27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…www.nature.com/scientificreports/ Cell type specific roles of RAS signalling in learning and memory. It has been shown that the RAS proteins are critically involved in learning and memory and synaptic plasticity 16,27 . Hyperactivation as well as hypoactivation of RAS-ERK signalling impairs learning and memory and synaptic plasticity 16,[27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…As previously shown, since RAS signalling networks are different between excitatory and inhibitory neurons, we speculate that KRAS-ERK signalling pathway is not coupled to pro-apoptotic signalling in inhibitory neurons. Previous studies have shown that mutations in genes involved in the RAS signalling pathway can alter the composition of cell types in both the developing and adult brain 16,39,40 . Changes in the ratio of excitatory and inhibitory neurons can subsequently distort the excitation-inhibition balance, which is critical for normal cognitive functions, including learning and memory 41,42 .…”
Section: Role Of Kras In Inhibitory Neurons Papale Et Al Showed Thamentioning
confidence: 99%
See 1 more Smart Citation
“…Rasopathies is a type of syndrome with phenotypic overlap. Mutations in the relevant functional genes and downstream signaling genes in this pathway lead to RAS-related diseases (1). NS(Noonan syndromes)are the most common Rasopathy disease.…”
Section: Introductionmentioning
confidence: 99%
“…On the opposite end of the spectrum, megalencephaly (MEG) is a neuronal disorder characterized by brain overgrowth (3 SD over the mean) 18 . The causes of megalencephaly are diverse, but activating mutations in the Pi3K-AKT-mTOR and the Ras-MAPK pathways have been identified as important underlying events [19][20][21] . Mouse and cerebral organoid models for these activated pathways demonstrated increased proliferation of radial glial cells leading to tissue overgrowth [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%